1999
DOI: 10.1080/10973439908408372
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Shaping Classes On Academic Skills, Self Care Skills and On-ward Behavior with Persons Who Are Cognitively Impaired and Chronic Psychiatric Inpatients

Abstract: Within the field of psychiatric rehabilitation, a growing body of evidence suggests the cognitive deficits associated with schizophrenia can exert a significant impact on an individual's rehabilitative potential. In this report we describe two studies centering around improvements in cognitive skills with multiply-impaired individuals with psychiatric disabilities residing in a rehabilitation program based on Paul and Lentz' (1977) social learning approach. In the first study, we compared improvements in readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In addition, published reports on attention shaping (Spaulding et al 1986; Menditto et al 1991; Silverstein et al 1998 b , 1999; Bellus et al 1999) have demonstrated dramatic improvements in attention span by consistently pairing primary or secondary reinforcers with the behavioral response of attentive and participatory behavior, even among so-called treatment-refractory state-hospital schizophrenia patients (reviewed in Silverstein 2000; Silverstein et al 2001). These procedures are also effective with outpatients in community settings (Skinner et al 2000).…”
Section: Need To Address Motivation Self-esteem and Affective Factorsmentioning
confidence: 99%
“…In addition, published reports on attention shaping (Spaulding et al 1986; Menditto et al 1991; Silverstein et al 1998 b , 1999; Bellus et al 1999) have demonstrated dramatic improvements in attention span by consistently pairing primary or secondary reinforcers with the behavioral response of attentive and participatory behavior, even among so-called treatment-refractory state-hospital schizophrenia patients (reviewed in Silverstein 2000; Silverstein et al 2001). These procedures are also effective with outpatients in community settings (Skinner et al 2000).…”
Section: Need To Address Motivation Self-esteem and Affective Factorsmentioning
confidence: 99%
“…The studies listed in table 1 introduce several practice innovations to clinicians working with schizophrenia patients. Novel treatment methods described in the table include (1) selection of staff members not normally involved in behavior therapy to serve as skills trainers (Wallace et al 1992; Smith et al 1996; Kopelowicz et al 1998; Liberman et al 1998), (2) individualization of training procedures for refractory patients (Eckman et al 1992; Kopelowicz et al 1997), (3) contingent reinforcement and shaping to improve patients’ responsiveness to skills training (Bellus et al 1999; Silverstein et al 1999 a , 1999 b ), (4) environmental and personnel interventions to increase generalization of skills (Hayes et al 1995; Liberman et al 1998; Blair et al, in press), (5) compliance-enhancing strategies to strengthen patients’ participation in treatment (Katz et al 1996; Weinhardt et al 1997; Ziedonis and George 1997; Liberman et al 1998), and (6) motivational techniques to bolster patients’ investment in behavior change (Halford et al 1995; Dobson 1996; Kelly et al 1997; Ziedonis and George 1997; Addington et al 1998). These innovations considerably broaden the set of techniques available to clinicians for introducing and tailoring learning-based therapies to patients with serious and persistent mental illness and for sustaining their compliance with treatment.…”
Section: Literature Updatementioning
confidence: 99%
“…These data support accumulating evidence on the relative independence of cognitive deficits and symptoms in schizophrenia (Green 1998). Bellus et al (1999) compared the academic skill performance of seven lower functioning patients in shaping classes to a group of seven higher functioning patients in traditional academic classes over a 9-month period. Most, but not all, patients in the Bellus et al study had chronic psychotic disorders.…”
Section: Shaping Attention Span As a Form Of Neurocognitive Rehabilitmentioning
confidence: 99%